Impact of Ultramicro Holding on Financial Performance and Business Sustainability - Abror, Ghozi; Muharam, Harjum (Research Horizon, 2024)
In order to encourage sustainable economic growth, the Government is trying to revive the Medium, Small and Micro Enterprises (MSMEs) and Ultra Micro (UMi) sectors, through the Ministry of SOEs. The presence of the UMi program through ultra-micro holding is expected to drive the development of micro-enterprises by providing easier access to financing, reduce poverty levels, improve community welfare, and contribute to sustainable national economic growth. The purpose of this study was to determine the impact of holding ultra-micro BRI, Pegadaian, and Reduction of State Capital (Pengurangan Modal Negara/PNM) on financial performance and business sustainability at BRI. The research method used is literature review with a qualitative approach and the data source used is secondary data. The data collection technique is done by means of documentation, namely data collection techniques through written materials published by the institution that is the object of research. The analysis technique is by data reduction, data presentation, and conclusion drawing. The results showed that the existence of ultra-micro holding had a real impact on increasing BRI's profit, showing the success of the integration strategy in supporting the growth and sustainability of BRI's business in the MSME sector.